Marital satisfaction as a function of mate value: an actor-partner model - Hromatko, Ivana (2013)
It has been proposed within the theoretical framework of evolutionary psychology that mate value, i.e. one’s value on the “partner market” influences both the mate selection process and the quality of a romantic relationship once it has been formed. The aim of this study was to test the relationship among perceived own and partner’s mate value and marital satisfaction. In order to explore the possible effect of cultural context on the structure of relationships among those variables, we conducted the study in two very different cultural contexts: 99 Iranian and 99 Croatian couples were included in a dyadic assessment. Croatian couples reported being more satisfied with their relationships than their Iranian counterparts. Accordingly, they also gave higher assessments of mate value of both themselves and their partners, as compared to the Iranians. We found an interesting culture x gender x object of assessment interaction: Croatian men and women and Iranian women perceived their partners to be of higher mate value than themselves, but Iranian men rated their partners to be of equal mate value as themselves. To explore the structure of relationships among mate value estimates and relationship satisfaction an actor – partner interdependence model was used. In both cultures own (actor) effects are generally stronger than partner ones, and one’s estimate of a partner’s mate value is generally the strongest predictor of relationship satisfaction. Again, the subsample of Iranian men showed a slightly different pattern of results than the rest of the sample, resulting in the lowest level of variance explained by the model. Cultural variations notwithstanding, this set of results indirectly confirms the evolutionary hypothesis about universal relevance of mate value in pair-bonding processes.